Therapeutic Potential of Ginger against Renal Injury Induced by Carbon Tetrachloride in Rats - Manal A. Hamed; Sanaa A. Ali; Nagy Saba El-Rigal (The Scientific World Journal)
The objective of this study was to evaluate the potential of successive ginger extracts (petroleum ether, chloroform, and ethanol) against nephrotoxicity induced by CCl4 in rats. The evaluation was done through measuring kidney antioxidant parameters: glutathione (GSH), lipid peroxides (LPO), and superoxide dismutase (SOD). Renal function test: urea, creatinine and serum protein values, were also evaluated. The work was extended to examine tissue inflammatory mediators, prostaglandin-E2 (PGE2), collagen content and the kidney histopathology. Severe alterations in all biomarkers were observed after injury with CCl4. Treatment with ginger extracts resulted in markedly decreased levels of LPO, PGE2, collagen and kidney function tests, while increased levels of GSH, SOD and serum protein were observed. In conclusion, extracts of ginger, particularly the ethanol, resulted in an attractive candidate for the treatment of nephropathy induced by CCl4 through scavenging free radicals, improved kidney functions, inhibition of inflammatory mediators, and normalizing the kidney histopathological architecture. Further studies are required in order to identify the molecules responsible of the pharmacological activity.